The characteristics of organic matter influence its interfacial interactions with MnO2 and catalytic oxidation processes - Zhang, S.; Gutierrez, L.; Niu, X.; Qi, F.; Croue, Jean-Philippe (Elsevier, 2018)
The influence of dissolved organic matter (DOM) properties on its interfacial interactions with MnO2and on catalytic oxidation processes was studied by Time-Resolved Dynamic Light Scattering (TR-DLS) and Atomic Force Microscopy (AFM) under varied solution conditions. Four DOM fractions of different characteristics (e.g., SUVA, hydrophobic character, structural properties) were selected. Bared-MnO2nanoparticles readily aggregated in NaCl and CaCl2solutions. Classic DLVO Theory successfully described critical coagulation concentrations and aggregation behaviors. In NaCl solution, DOM adsorbed on MnO2nanoparticles and provided electrosteric stabilization. The two DOM fractions of higher hydrophobic (HPO) character were more efficient in decreasing the aggregation rates. Enhanced MnO2aggregation was observed at high Ca2+concentrations due to charge screening and cation bridging between carboxyl groups in DOM structures. The addition of oxidant (H2O2) induced a high aggregation of bared-MnO2nanoparticles, possibly due to the release of Mn2+(i.e., complexation mechanisms) and generation of reactive species (O2[rad]-, HO2-, and H[rad]). Contrasted with their hydrophilic (HPI) counterparts, HPO isolates adsorbed on MnO2significantly decreased the catalytic oxidation processes between H2O2/MnO2; suggesting a more efficient and stronger DOM coating. Interfacial forces measured by AFM, showed weaker interactions between HPI isolates and MnO2; suggesting unfavorable polar interactions. Conversely, the high adhesion forces between MnO2/HPO isolate would indicate stronger bonds and hydrophobic interactions. This study provided a nanoscale understanding of the impact of DOM characteristics on: a) performance of the MnO2coated ceramic membranes in water treatment, and b) biogeochemical cycle of Mn-oxides in the environmental.